Achievement Motivation, Affiliation Motivation, and Student Learning Behavior During The Covid-19 Pandemic: A Structural Equation Model - Wiryo Nuryono (Jurnal Inspirasi Pendidikan, 2022)
Learning behavior can be driven by motivation, when the quality of this motivation is high it will have a positive impact on welfare, but when motivation is of low quality it will have a detrimental impact on welfare. This study aims to determine the relationship between achievement motivation, affiliation motivation, and student learning behavior during the Covid-19 pandemic. Research design correlation with SEM analysis techniques. The subjects that will be used consist of 2941 junior high school students who were selected using the cluster random sampling technique. The research data was taken using 3 psychological scales, namely achievement motivation, affiliation motivation, and learning behavior. The data that has been collected is then analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) assisted by Warp – PLS version 7.0. The results of the analysis show that the coefficient of achievement motivation on learning behavior is 0.64. It shows that achievement motivation is significantly correlated. The coefficient of affiliated motivation on learning behavior is 0.1. It shows that affiliation motivation is influential but not significant, even though affiliation motivation supports learning behavior.